Different pitches for different stages of entrepreneurial development: the practice of pitching to business angels. Issue 3 (14th March 2020) - Teague, Bruce; Gorton, M. David; Liu, Yanxin
ABSTRACT: In this paper, we draw upon social practice theory as a lens through which to challenge commonly held assumptions about the practice of pitching. This study presents evidence suggesting that the commonly studied investment pitch, may in fact be part of a larger relational practice that plays out across time as entrepreneurs and their new businesses develop. We present findings from twenty-seven months of participant observation in an active angel investment organization located in the United States. Based on our observations, we discuss four types of pitch: developmental, pre-investment, investment, and update.